Time series of freshwater macroinvertebrate abundances and site characteristics of European streams and rivers - Welti, Ellen A R; Bowler, Diana E; Sinclair, James S; Altermatt, Florian; Álvarez-Cabria, Mario; Amatulli, Giuseppe; Angeler, David G; Archambaud, Gaït; Arrate Jorrín, Iñaki; Aspin, Thomas; Azpiroz, Iker; Baker, Nathan Jay; et al. (Scientific data, 2024)
Freshwater macroinvertebrates are a diverse group and play key ecological roles, including accelerating nutrient cycling, filtering water, controlling primary producers, and providing food for predators. Their differences in tolerances and short generation times manifest in rapid community responses to change. Macroinvertebrate community composition is an indicator of water quality. In Europe, efforts to improve water quality following environmental legislation, primarily starting in the 1980s, may have driven a recovery of macroinvertebrate communities. Towards understanding temporal and spatial variation of these organisms, we compiled the TREAM dataset (Time seRies of European freshwAter Macroinvertebrates), consisting of macroinvertebrate community time series from 1,816 river and stream sites (mean length of 19.2 years and 14.9 sampling years) of 22 European countries sampled between 1968 and 2020. In total, the data include >93 million sampled individuals of 2,648 taxa from 959 genera and 212 families. These data can be used to test questions ranging from identifying drivers of the population dynamics of specific taxa to assessing the success of legislative and management restoration efforts.
Keywords: kvalita vody; Rivers; sladká voda; populační dynamika; Ecosystem; bezobratlí; řeky; Europe; Animals; Water Quality; biodiverzita; Fresh Water; Population Dynamics; zvířata; Evropa; Invertebrates; ekosystém; Biodiversity